Theoretical Vibration Analysis on 600 Wh Energy Storage Flywheel Rotor—Active Magnetic Bearing System - Jing-na Liu; Zheng-yi Ren; Shan-wei Wu; Yin-long Tang (International Journal of Rotating Machinery)
This paper shows a theoretical vibration analysis regarding the controller’s parameters and the gyroscopic effect, based on a simplified rotordynamic model. Combined with 600 Wh energy storage flywheel rotor system mathematical model, the Campbell diagram of the rotor system was obtained by the calculation of the whirl frequency under different parameters of the controller in MATLAB to analyze the effect of the controller parameter on the whirl frequency and to limit the operating speed and acceleration or deceleration of the rotor. The result of the analysis can be used to set the support position of the rotor system, limit the ratio of transverse moment of inertia and the polar moment of inertia, and direct the flywheel prototype future design. The presented simplified rotordynamic model can also be applied to rotating machines.